Between memory and matter: Italy and the transnational dimensions of public art - Bond, E (Taylor and Francis, 2022)
This article identifies a set of precarious, temporary, and travelling forms of commemoration that have been expressed in recent public artworks connected to Italy, and proposes them as case studies that together can enhance our understanding of how transnational memory is formed and functions across borders. These complex processes of memory-making are illustrated through a comparative analysis of Wes Anderson’s Bar Luce (2015), Thomas Hirschhorn’s Gramsci Monument (2013), and Muna Mussie’s Oblio (2021). The selected works, which together add transnational nuance to James E. Young’s concept of the ‘counter-monument’, enshrine the creativity which can reside in acts of forgetting and misremembering, in experiencing things second-hand or at a distance, and in re-materialising memory through tropes of ephemerality, portability, and dislocation.